2(2m-3)=7(m+6)

Simple and best practice solution for 2(2m-3)=7(m+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2m-3)=7(m+6) equation:



2(2m-3)=7(m+6)
We move all terms to the left:
2(2m-3)-(7(m+6))=0
We multiply parentheses
4m-(7(m+6))-6=0
We calculate terms in parentheses: -(7(m+6)), so:
7(m+6)
We multiply parentheses
7m+42
Back to the equation:
-(7m+42)
We get rid of parentheses
4m-7m-42-6=0
We add all the numbers together, and all the variables
-3m-48=0
We move all terms containing m to the left, all other terms to the right
-3m=48
m=48/-3
m=-16

See similar equations:

| 26+y=16 | | -v+9v=6v+3 | | 6x-64=4x-32 | | x-5x-10=5+2x-7 | | 3w+6+2w=1 | | -4+6r=8 | | 14.8x=30.2 | | 2+24x=25x | | -4(9-t)=0 | | 2(3a+4)=17 | | 8(3x+9)=6x+252 | | 25m+700=6700 | | x²+10x+20=0 | | 6x+2x+34=58 | | -5/9=x/18 | | b/7=2.5 | | -7(n+2)=-14-14n | | 11r-r-r-3=15 | | 98x+451=36x+1195 | | 10+2=4(7x-3) | | 28x=-35 | | -2x-4-3x=-10 | | 5(x+6)=4x+2x-10 | | 4(1-x)x3x=2(x-1) | | 0.5m—3.5=3m+6.5 | | 3q-7=17 | | -b-(13=4b)=-3(5-9b)+2 | | x+2.9=6.3 | | 6+x=-7+2x | | 28+7x=49+7x | | -17(y+3)+6(4y-3)=6(y-3)+14 | | 1x=11.75 |

Equations solver categories